Using concepts of proportional relationships, it is found that the solution of the system is (0,0).
[tex]y = kx[/tex]
In this problem, the system consists of two different proportional relationships, that is:
[tex]y = k_1x[/tex]
[tex]y = k_2x[/tex]
[tex]k_1 \neq k_2[/tex]
Hence, equaling both equations for y, we have that:
[tex]k_1x = k_2x[/tex]
Simplifying by x:
[tex]k_1 = k_2[/tex]
Which is never true, hence, the only solution is (0,0).
You can learn more about proportional relationship at brainly.com/question/13550871